Study on Self-Cleaning Concrete Using Nano-liquid TiO2 - Vignesh, T; Sumathi, A; Saravana Raja Mohan, K (International Journal of Engineering and Technology, 2018)
The present work explores to study the compressive strength and self-cleaning properties of the concrete by the applications of nano-liquid TiO2 on fresh concrete with different dosages (0, 2.5, 5.0, 7.5 ml) and single, double, and triple layer coating of nano-liquid Tio2 on the hardened concrete surfaces. Cement was partially replaced with Fly ash by In this study cement was replaced with 30% fly ash and to examine self cleaning properties of concrete by using Rhodamine-B dye (RhB) discoloration test under Sunlight/UV light visual observation. Concrete samples with photocatalytic nano-liquid Tio2 was mixed with fresh concrete (NF) showed enhanced compression strength by increasing the dosages when compared to the nano-liquid Tio2 was coated on the surface of the hardened concrete (NH). Self cleaning ability of NH of samples showed better results in cleaning ability than NF samples.Â Â Â